Sedative and cardiopulmonary effects of dexmedetomidine infusions randomly receiving, or not, butorphanol in standing horses - Medeiros, Luíza Quintão [UNESP]; Gozalo-Marcilla, Miguel [UNESP]; Taylor, Polly M.; Campagnol, Daniela [UNESP]; De Oliveira, Flávia Augusta [UNESP]; Watanabe, Marcos Jun [UNESP]; De Araujo Aguiar, Antonio José [UNESP] (Wiley, 2017)
Dexmedetomidine (DEX) alone, or combined with butorphanol (BUT), may be administered by constant rate infusions (CRIs) in standing horses. This blinded, randomised, crossover study in six healthy adult horses aimed to determine the sedative and cardiopulmonary effects of DEX (dexmedetomidine (3.5 μg/kg+5 μg/kg/hour CRI) and DEX/BUT (dexmedetomidine (3.5 μg/kg+3.5 μg/kg/hour CRI) and butorphanol (20 μg/kg+24 μg/kg/hour CRI)). Head height above ground (HHAG), ataxia, responses to tactile/auditory stimuli and cardiopulmonary variables were recorded before, at 5/15/30/60/90 minutes and after CRIs terminated (15/30/60 minutes). Repeated measures analysis of variance with Tukey-Kramer test were used for cardiopulmonary values (mean±SD) and HHAG reduction (per cent), and Friedman's and Dunn's for non-parametric data (P<0.05). Maximum HHAG reductions of 54 per cent (DEX) and 58 per cent (DEX/BUT) occurred at 15 minutes, with ataxia for 15 minutes in both treatments. Responses to stimuli were reduced for 30 minutes in both treatments, and auditory up to 60 minutes in DEX. Cardiopulmonary effects typical of α 2 -agonists were observed, with no differences between treatments. At the doses and rates reported here, both regimens provided clinically sufficient sedation for only 30 minutes.
Keywords: butorphanol; constant rate infusion; dexmedetomidine; equine; standing horse